Output-Boundary Regulation Using Event-Based Feedforward for Nonminimum-Phase Systems - Arom Boekfah (2018)
© 2015 IEEE. This paper seeks to bound the effects of disturbances on the output by considering an output-boundary regulation (OBR) problem. If a priori (preview) information of the disturbance is available, feedforward approaches can overcome the limits of feedback methods for nonminimum-phase systems. The main contribution of this paper is to develop a feedforward-based control approach for nonminimum-phase systems when the disturbance is not known a priori. Furthermore, the performance of the proposed approach is quantified by providing the acceptable disturbance for a given output-error bound. Simulation results for a benchmark flexible-structure example are presented to show substantial performance improvement with the proposed optimal OBR approach compared with dc-gain-based or step-input-based approaches.